2016
DOI: 10.3390/molecules21111499
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Synthesis of Novel Partial Esters of a Bioactive Dihydroxy 4-Methylcoumarin by Rhizopus oryzae Lipase (ROL)

Abstract: Abstract:Highly regioselective acylation has been observed in 7,8-dihydroxy-4-methylcoumarin (DHMC) by the lipase from Rhizopus oryzae suspended in tetrahydrofuran (THF) at 45 • C using six different acid anhydrides as acylating agents. The acylation occurred regioselectively at one of the two hydroxy groups of the coumarin moiety resulting in the formation of 8-acyloxy-7-hydroxy-4-methylcoumarins, which are important bioactive molecules for studying biotansformations in animals, and are otherwise very difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The results confirmed that the acetylated products were 8AMC and DAMC, which is consistent with previously published nuclear magnetic resonance (NMR) results. 31 Acylation of 7,8-Dihydroxy-4-methylcoumarin through the addition of acid anhydride resulted in the synthesis of 8-Acetoxy-7-hydroxy-4-methylcoumarin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results confirmed that the acetylated products were 8AMC and DAMC, which is consistent with previously published nuclear magnetic resonance (NMR) results. 31 Acylation of 7,8-Dihydroxy-4-methylcoumarin through the addition of acid anhydride resulted in the synthesis of 8-Acetoxy-7-hydroxy-4-methylcoumarin.…”
Section: Resultsmentioning
confidence: 99%
“…The results confirmed that the acetylated products were 8AMC and DAMC, which is consistent with previously published nuclear magnetic resonance (NMR) results. 31 Effects of DHMC, 8AMC, and DAMC on the Viability of RAW 264.7 Cells and Their Ability to Reduce NO Production RAW 264.7 cells stimulated with LPS were incubated with various concentrations of DHMC, 8AMC, and DAMC to determine their cytotoxicity. The results of 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays revealed that no compound was cytotoxic up to a concentration of 25 µM (Figure 1A).…”
Section: Nmr Spectroscopymentioning
confidence: 99%